OGM: caso de papa y manzana que no se oxida - Garro-Monge, Giovanni; Méndez, Laura (Cámara Costarricense de la Industria Alimentaria., 2016)
Genetically modified organisms are those foods that are improved through biotechnology, where they are modified from one to four genes by genetic engineering. Producing these products improves traits such as nutritional quality, modifies metabolic pathways and resistance to pests. The present article presents four techniques of modification of food crops, which are the traditional cross, mutagenesis, interfering RNA and, finally, transgenesis. In addition, it explains how the crops are genetically modified, with the example of potato and apple.
Keywords: Modificación genética; Resistencia a las plagas; Genes; Biotecnología; Cultivos transgénicos; Ingeniería genética; Research Subject Categories::TECHNOLOGY::Chemical engineering::Food technology; ADN; Genetic modification; Pest resistance; Biotechnology; Transgenic crops; Genetic engineering